Assessing STEM Literacy: Development and Implementation of a Geoscience Project-Based Evaluation - Najah, Triwid Syafarotun; Luvia Ranggi Nastiti (Journal of Education Reseach and Evaluation, 2025)
In the context of global environmental challenges, this study aims to identify significant gaps related to the absence of a comprehensive assessment tool to evaluate STEM literacy within the framework of a geoscience project. The subjects of the study included a population of 254 respondents, with sampling using a simple random sampling technique that resulted in a minimum sample of 155 respondents. The data collection method was carried out through a systematic problem analysis technique, including needs analysis and field research. Data collection was designed to obtain accurate and representative information by considering an error rate (e) of 0.05. The data analysis method used Confirmatory Factor Analysis (CFA) with Lisrel software, which tested the structural legitimacy of the research data. The feasibility test criteria included the Goodness of Fit Index (GFI), Adjusted Goodness of Fit Index, and Root Mean Square Error of Approximation. The results showed very strong psychometric characteristics of the instrument, with content validity reaching an Aiken coefficient of 0.99, construct validity with a good model fit index, and construct reliability (CR) of 0.83. The instrument consists of ten items covering four main STEM literacy indicators: Science, Technology, Engineering, and Mathematics. The conclusion of the study confirms that this instrument is not just an assessment tool but a transformative mechanism to develop students' interdisciplinary skills in facing the challenges of the 21st century. The contribution of this study is significant in providing an epistemological foundation for STEM education, emphasizing the importance of interdisciplinary literacy in preparing a generation that is able to compete in an increasingly complex global landscape.